2018
DOI: 10.1021/acs.estlett.8b00113
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhalation Bioaccessibility of Phthalate Esters and Alternative Plasticizers Present in Indoor Dust Using Artificial Lung Fluids

Abstract: Phthalate esters (PEs) are plasticiser additives imparting durability, elasticity and flexibility to consumer products. The low migration stability of PEs along with their ubiquitous character and adverse health effects to humans and especially children has resulted in their classification as major indoor contaminants. This study assesses inhalation exposure to PEs via indoor dust using an in vitro inhalation bioaccessibility test (i.e. uptake) for of dimethyl phthalate (DMP), diethyl phthalate (DEP) and di-(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…In the present study, the result indicated the effects of OC and EC on bioaccessibility in lung uid depend on these physicochemical properties, differing from that for oral bioaccessibility (emission source dependent). Similar correlation was also found for the inhalation bioaccessibility of phthalate esters in house dust as shown in a recent study (Kademoglou et al 2018). Signi cant associations with OC and EC were also found for the hydrophobic OPEs (Table 1).…”
Section: Inhalation Bioaccessibility and In Uencing Factorssupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, the result indicated the effects of OC and EC on bioaccessibility in lung uid depend on these physicochemical properties, differing from that for oral bioaccessibility (emission source dependent). Similar correlation was also found for the inhalation bioaccessibility of phthalate esters in house dust as shown in a recent study (Kademoglou et al 2018). Signi cant associations with OC and EC were also found for the hydrophobic OPEs (Table 1).…”
Section: Inhalation Bioaccessibility and In Uencing Factorssupporting
confidence: 88%
“…Liu et al (2019) recently observed considerably low bioaccessibility (< 0.75%) of PAHs in biochar. Inhalation bioaccessibility of phthalate esters in house dust (Kademoglou et al 2018) was similar to that for OPEs in this study.…”
Section: Inhalation Bioaccessibility and In Uencing Factorssupporting
confidence: 79%
See 1 more Smart Citation
“…Considering in vitro assays numerous published protocols demonstrated their ability to predict in vivo results for trace metals (ANSES, 2019). However, most of these frequently used methodologies minimize bioavailability of lipophilic POPs (Kademoglou et al, 2018;Li et al, 2016), and solubilization of these hydrophobic POPs was pointed out as one of the most limiting step (ANSES, 2019;Collins et al, 2013;Kademoglou et al, 2018;Li et al, 2016). In this frame, novel methodologies implement sorptive phases to enhance the solubilization and mobilization of POPs also reproducing the on-going absorption during the intestinal phase.…”
Section: Bioaccessibility and Relative Bioavailability As Complementa...mentioning
confidence: 99%
“…However, in vitro oral bioaccessibility studies of organic pollutants in particulate matter were not found in the literature, while there were some studies applied to indoor/outdoor dust and soils for organic compounds, i.e. PAHs (Tang et al 2006;Kang et al 2011;Collins et al 2013;Li et al 2015;Kademoglou et al 2018a), organophosphate flame retardants (Quintana et al 2017), semi-volatile organic compounds (Raffy et al 2018), polychlorinated biphenyls (Wang et al 2013) and polybrominated diphenyl ethers (Yu et al 2011;Kademoglou et al 2018b;Gao et al 2019b). The stringent analytical requirements (target pollutants enrichment, due to the low levels; and pollutant isolation from the synthetic fluids matrix) for organic pollutant quantification in bioaccessible/bioavailable fractions might explain the scare information.…”
Section: Introductionmentioning
confidence: 99%